Experimental Infection of Syrian Hamsters With Aerosolized Nipah Virus. (15th June 2018) - Escaffre, Olivier; Hill, Terence; Ikegami, Tetsuro; Juelich, Terry L; Smith, Jennifer K; Zhang, Lihong; Perez, David E; Atkins, Colm; Park, Arnold; Lawrence, William S; Sivasubramani, Satheesh K; Peel, Jennifer E; et al.
Abstract : Small-particle aerosolized Nipah virus Malaysia strain remains infectious and causes similar clinical manifestations of disease in the Syrian hamster model as using the corresponding liquid inoculum. Nipah droplets could therefore play a role in human-to-human transmission by close contact. Abstract: Background: Nipah virus (NiV) is a paramyxovirus (genus Henipavirus ) that can cause severe respiratory illness and encephalitis in humans. Transmission occurs through consumption of NiV-contaminated foods, and contact with NiV-infected animals or human body fluids. However, it is unclear whether aerosols derived from aforesaid sources or others also contribute to transmission, and current knowledge on NiV-induced pathogenicity after small-particle aerosol exposure is still limited. Methods: Infectivity, pathogenicity, and real-time dissemination of aerosolized NiV in Syrian hamsters was evaluated using NiV-Malaysia (NiV-M) and/or its recombinant expressing firefly luciferase (rNiV-Fluc NP ). Results: Both viruses had an equivalent pathogenicity in hamsters, which developed respiratory and neurological symptoms of disease, similar to using intranasal route, with no direct correlations to the dose. We showed that virus replication was predominantly initiated in the lower respiratory tract and, although delayed, also intensely in the oronasal cavity and possibly the brain, with gradual increase of signal in these regions until at least day 5–6 postinfection. Conclusion: Hamsters infected with small-particle aerosolized NiV undergo similar clinical manifestations of the disease as previously described using liquid inoculum, and exhibit histopathological lesions consistent with NiV patient reports. NiV droplets could therefore play a role in transmission by close contact.